Tratamiento psicológico, según la terapia racional emotiva - Amorós, Víctor (1991)
The author presents the study of a 30 year old patient, a single male, who suffers from anxiety, depression and difficulties to cope with his work. The most important aspects of the patient's history and reason for referral are discussed. Some rational emotive therapy sessions are described.